2021
DOI: 10.3390/cancers13133326
|View full text |Cite
|
Sign up to set email alerts
|

A New Anatomic and Staging-Oriented Classification of Radical Hysterectomy

Abstract: The current understanding of radical hysterectomy more is centered on the uterus and little is being discussed about the resection of the vaginal cuff and the paracolpium as an essential part of this procedure. This is because that the current classifications of radical hysterectomy are based only on the lateral extent of resection. This way is easier to be understood but does not reflect the anatomical and surgical conception of radical hysterectomy and the three-dimensional ways of tumour spreading, neither … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…We focus on the steps to dissect, visualize, and highlight the sympathetic trunks, the superior hypogastric plexus, the abdominal aortic plexus, and the intermesenteric nerves (Figure 1) during para-arotic lymph node dissection using an open approach. Other studies from our study group confirmed the feasibility of nerve sparing surgery during radical hysterectomy for cervical cancer and explained the precise anatomy of the pelvic autonomic nervous system 7–9. Nerve sparing para-aortic lymph node dissection is feasible and safe in gynecological cancer cases when following the steps outlined in the video for careful dissection of the aortic and superior hypogastric plexus 1 6.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We focus on the steps to dissect, visualize, and highlight the sympathetic trunks, the superior hypogastric plexus, the abdominal aortic plexus, and the intermesenteric nerves (Figure 1) during para-arotic lymph node dissection using an open approach. Other studies from our study group confirmed the feasibility of nerve sparing surgery during radical hysterectomy for cervical cancer and explained the precise anatomy of the pelvic autonomic nervous system 7–9. Nerve sparing para-aortic lymph node dissection is feasible and safe in gynecological cancer cases when following the steps outlined in the video for careful dissection of the aortic and superior hypogastric plexus 1 6.…”
Section: Discussionsupporting
confidence: 69%
“…Other studies from our study group confirmed the feasibility of nerve sparing surgery during radical hysterectomy for cervical cancer and explained the precise anatomy of the pelvic autonomic nervous system. [7][8][9] Nerve sparing para-aortic lymph node dissection is feasible and safe in gynecological cancer cases when following the steps outlined in the video for careful dissection of the aortic and superior hypogastric plexus. 1 6 Larger prospective trials are planned to assess the effects of this technique on postoperative functional patient reported outcomes.…”
mentioning
confidence: 99%
“…The radical hysterectomies were performed nerve-sparingly according to our technique described in a previous study [ 28 ]. The radicality was adjusted to the tumor volume, localization, infiltration in the vagina, and FIGO-stage in accordance with the Muallem classification of radical hysterectomy [ 30 ]. The statistical analysis was performed at the Charité Medical University Berlin.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the evolution of the radical hysterectomy technique [7][8][9][10][11][12] since its first description in 1912 [13] reflects the challenges that have been associated with this surgery. Very recently, a new classification of radical hysterectomy has been postulated considering the lateral extent of parametrium resection and the depth of resection of the resected vaginal vault without or with its threedimensional paracolpium [14]. However, the impact of surgical practice on oncological outcomes after robot-assisted radical hysterectomies remains unclear.…”
Section: Introductionmentioning
confidence: 99%